Feminist responses to sexual harassment in academia: voice, solidarity and resistance through online activism. (1st February 2020) - Anitha, Sundari; Marine, Susan; Lewis, Ruth
Abstract : This paper takes as its starting point the compilation and circulation online of a list naming alleged sexual harassers in Indian academia in order to examine broader questions about the nature of online activism to address gender-based violence. Set against the historical silencing of women who speak about violence as well as institutional mechanisms to address this issue through due process, we examine the meaning, impact and limitations of this list, which generated considerable discord and debate within feminists in India. In doing so, we consider the place of these new forms of collective actions and expressions of solidarity within the broader feminist campaigns to resist violence.